On correlation functions of BPS operators in 3dN=6 superconformal theories - Liendo, P; Meneghelli, C; Mitev, V (Springer, 2016)
We introduce a novel harmonic superspace for 3dN=6 superconformal field theories that is tailor made for the study of correlation functions of BPS operators. We calculate a host of two- and three-point functions in full generality and put strong constraints on the form of four-point functions of some selected BPS multiplets. For the four-point function of 12-BPS operators we obtain the associated Ward identities by imposing the absence of harmonic singularities. The latter imply the existence of a solvable subsector in which the correlator becomes topological. This mechanism can be explained by cohomological reduction with respect to a special nilpotent supercharge.